2017
DOI: 10.1017/jlg.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring global and local patterns in the correlation of geographic distances and morphosyntactic variation in Swiss German

Abstract: Using data from a Swiss German dialect syntax survey, this study aims to explore, in a spatially differentiated manner, the correlation between dialectal variation and geographic distances. A linguistic distance was expressed by a measure aggregated from 60 survey questions. To operationalize the possibility of language contact, Euclidean distance, as well as travel times in 2000, 1950 and 1850 between survey sites were used. Going beyond previous work by others, we also explore the covariation of geographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…I hope to pursue such trials in future research. On the other hand, some subjects, especially on the relationships of different methods and language data (Goebl 2005(Goebl , 2006Heeringa and Nerbonne 2001;Jeszenszky et al 2017;Nerbonne and Kleiweg 2007), remain for future study.…”
Section: Discussionmentioning
confidence: 99%
“…I hope to pursue such trials in future research. On the other hand, some subjects, especially on the relationships of different methods and language data (Goebl 2005(Goebl , 2006Heeringa and Nerbonne 2001;Jeszenszky et al 2017;Nerbonne and Kleiweg 2007), remain for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Holman et al [49], inspired by population genetics [50], explicitly associate the concept of 'isolation by distance' among the world's languages with the situation faced by dialectology. The axiomatic role of geography structuring language, phrased by Nerbonne and Kleiweg [51] (p. 154), which practically describes spatial autocorrelation in dialectal variation, was tested in numerous studies, e.g., [15,21,26,41,52,53]. Nerbonne and Kleiweg's postulate, "geographically proximate varieties tend to be more similar than distant ones", is, in effect, the linguistic adaptation of Tobler's first law of geography [54].…”
Section: Introductionmentioning
confidence: 99%
“…Although Gooskens [21,59] and Jeszenszky et al [53] confirmed the superior explanatory power of travel times, multiple studies for different languages [52,57,60] have found that travel times are not a better predictor for dialectal variation than Euclidean distance. Regarding historical contact, Huisman [14] showed that mainland Japanese displays an isolation-by-distance pattern, while Ryukyuan varieties display a typical isolation-by-colonisation pattern.…”
Section: Introductionmentioning
confidence: 99%
“…One of dialectometry's most important foci is the quantitative expression of linguistic differences across the surveyed locations (e.g., Seguy, 1971;Goebl, 1982;Nerbonne, 2010) and attributing these 'linguistic distances' to some geographical measures which usually account for the possibility of contact and isolation between speakers of a language (such as geographic distances, travel times, and gravity-like urban hierarchy relations). Most of the research on Japanese dialects focused, however, on the linguistic relations themselves, and did not often account quantitatively for the underlying factors assumed to affect dialectal variation.. Based on previous work in linguistic geography (e.g., Gooskens, 2005;Spruit, 2006;Szmrecsanyi, 2012;Jeszenszky et al, 2017;Sieber, 2017) it is possible to hypothesise the following patterns with regards to explaining linguistic variation based on language-external factors. Geographic distances will explain a considerable amount of the variation, due to the fact that usually the linguistic variables queried in dialect atlases are assumed to exhibit spatial variation.…”
mentioning
confidence: 99%
“…Digital elevation models will be used to find the most probable natural contact paths between survey sites, which are supposed to have been used for hundreds of years before the industrial revolution, assumed to form the local linguistic differences for a long time. Correlation with modern travel times, an informed guess about today's possible contact paths will also be calculated (similarly to Gooskens, 2005 andJeszenszky et al, 2017), along with historical travel times (sourced from georeferencing historical maps and network analysis of Edo-era port data), fitting more the time when the respondents grew up, acquiring their mother tongue. We will implement Trudgill's (1974) linguistic gravity theory, which supposes that linguistic influence between communities is arranged in a way similar to gravitational interaction, with population playing the role of mass.…”
mentioning
confidence: 99%